Karakteristik Analisis Spektrofotometri IR Ekstrak Batang Kebiul (Caesalpinia bonduc (L.) Roxb) dengan Variasi Pelarut pada Maserasinya - Desy Amalia; Septi Wulandry; Karina Primtyas; Delta Baharyati (Jurnal Pharmacopoeia, 2026)
Caesalpinia bonduc (L.) Roxb is known to contain various secondary metabolites with antioxidant, anti-inflammatory, and antimicrobial properties. Differences in solvent polarity influence the types of compounds extracted; therefore, functional group profiling is essential to identify active constituents. This study aimed to compare the FTIR-ATR spectral profiles of C. bonduc stem extracts obtained using three solvents of different polarities: ethanol, ethyl acetate, and n-hexane. Extraction was carried out by maceration, and characterization was performed using a Bruker Alpha II FTIR spectrophotometer within the 4000–400 cm⁻¹ range. The ethanol extract exhibited strong absorption at 3430 cm⁻¹ (–OH) and 1635 cm⁻¹ (C=O), indicating polar compounds such as flavonoids and phenolics. The ethyl acetate extract showed distinctive bands at 1740 cm⁻¹ (C=O ester), while the n-hexane extract displayed peaks at 2922–2858 cm⁻¹ (C–H), associated with non-polar compounds such as fatty acids and terpenoids. Variations in absorption bands among the three extracts confirm that solvent polarity significantly affects the extracted chemical composition. The FTIR-ATR technique proved effective for rapid and non-destructive characterization of bioactive compounds in medicinal plant extracts.